Postoperative Imaging of Ulnar Wrist Pain - Cerezal, Luis; Llopis, Eva; Canga, Ana; Piñal, Francisco Del (Seminars in Musculoskeletal Radiology, 2021)
Ulnar wrist pain, caused by a broad spectrum of bone and soft tissue injuries, is the most common clinical condition of the wrist. Multiple surgical techniques and their variants in the treatment of these injuries are constantly evolving. Postoperative evaluation of the wrist for many surgeons is limited to serial clinical and radiographic monitoring. However, imaging methods such as ultrasonography, computed tomography (CT), magnetic resonance imaging (MRI), and arthrographic techniques (arthrographic CT and arthrographic MRI) play a fundamental role in diagnosing and managing postsurgical complications.The several critical aspects in evaluating the postsurgical wrist imaging spectrum are familiarity with the surgical techniques, knowledge of the original clinical problem, understanding the strength and limitations of the different radiologic modalities, and effective communication between surgeon and radiologist.
Keywords: postoperative imaging; magnetic resonance imaging; wrist; wrist injuries; postoperative complications